2003
DOI: 10.1080/0965254032000133449
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the consequences of market orientation in China

Abstract: Recent literature suggests that the relationship between market orientation and business performance may be moderated by the nature of the external environment. While the conceptual arguments for such a relationship are well established, empirical evidence on the precise nature of this link has been both limited and ambiguous. The current paper provides further evidence on the nature of the links between market orientation, the environment and performance through a comparative analysis of two business sectors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 55 publications
5
38
0
Order By: Relevance
“…Crosssectional data were used in the study to collect information from executives because it is the most common technique and provides inexpensive, quick, accurate and efficient means of collecting information about a population (Robson, 2002;Zikmund and Babin, 2010). The executives at these hotels who are exposed to strategic decisions of these hotels were engaged in the study (Qu and Ennew, 2003). Subjective scales of hotel performance (customer satisfaction, customer loyalty, and customer retention) were used in measuring business performance (Qu and Ennew, 2003;Urde et al, 2013).…”
Section: Positioning and Hotel Performancementioning
confidence: 99%
See 3 more Smart Citations
“…Crosssectional data were used in the study to collect information from executives because it is the most common technique and provides inexpensive, quick, accurate and efficient means of collecting information about a population (Robson, 2002;Zikmund and Babin, 2010). The executives at these hotels who are exposed to strategic decisions of these hotels were engaged in the study (Qu and Ennew, 2003). Subjective scales of hotel performance (customer satisfaction, customer loyalty, and customer retention) were used in measuring business performance (Qu and Ennew, 2003;Urde et al, 2013).…”
Section: Positioning and Hotel Performancementioning
confidence: 99%
“…Hotels can also grow with a more customer-oriented approach like market orientation and positioning that can enhance hotel performance (Tajeddini, 2010). Although, there are contributions on hotel market orientation (Qu and Ennew, 2003;Sin et al, 2005;Wang et al, 2012) and hotel positioning (O'neill and Mattila, 2006;Lee and Back, 2010), these studies do not purposefully consider the complementary effects of market orientation and hotel positioning. This study therefore examines the joint effects of market orientation and positioning on the performance of star-rated (luxury) hotels in Ghana.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To determine whether the relationship between market orientation and organisational performance is moderated by the nature of the external environment, Qu and Ennew (2003) found that degree of competitive intensity and market turbulence had little if any impact on the relationship. The research also found a positive relationship between degree of market orientation and customer satisfaction and corporate social responsibility.…”
Section: Consequences Of Market Orientationmentioning
confidence: 99%